Willingness to Communicate and Its Influencing Factors among Indonesian Pre-Service Teachers - Indry Widyasti Anwar; Min Jung Jee; Sutisno Adam; Sartika Sailuddin (Journal of Languages and Language Teaching, 2021)
Willingness to communicate (WTC) can be defined as the readiness of a language learner to enter communication situation. This study aims to identify factors affecting pre-service teachers’ WTC and to explore their perspective on the importance of WTC in relation to the study program. The study implemented both quantitative and qualitative method in order to gain deeper understanding from questionnaires and interview data. Questionnaires were used to explain interrelated relationship between variables affecting WTC among pre-service teachers. Interview data were used to report their perspective on the significance of WTC in relation to their study program.  The result inferred that pre-service teachers have relatively high WTC. Motivation variable  scale  indicated direct positive relation to pre-service teachers’ WTC while anxiety showed a negative relationship.  Language learning beliefs items were reported to be moderately agreed upon among pre-service teachers influencing their WTC. Interview result inferred that pre-service teachers mostly agreed upon the significance of enhancing WTC among learners. Implications for learning as a result from this study suggested that teachers and curriculum makers to improve teaching techniques and approaches in order to enhance learners’ WTC.